Heuristics in Mutual Fund Consumers' Willingness‐to‐Invest: An Experimental Approach. Issue 4 (30th September 2019) - Lavin, Jaime F.; Valle, Mauricio A.; Magner, Nicolás S.
Abstract : This paper improves the understanding of heuristics in the choice of mutual funds. We analyze the effect of price‐quality relationship and anchors as heuristics on the evaluation of the willingness‐to‐invest. We perform two studies with graduate students who possess a medium–high level of financial literacy in Chile. In the first study, we find that willingness‐to‐invest increases (decreases) when subjects observe (do not observe) in the market a positive relationship between expense ratios (price) and service quality. In the second study, in the presence of an anchor, the reference price obtained by individuals from the market information loses relevance and the anchor effect predominates. Our results confirm that participants, as consumers of financial services, apply heuristics as groundwork for their investment decisions. These heuristics as a decision making process are useful but do not always lead to the choice of the lowest cost alternative with the highest possible service quality.